KAMSEUPAI (KAMUS SAKU SEBAGAI MEDIA PEMBELAJARAN INOVATIF) BERBASIS BAHASA GORONTALO BAGI PARA SISWA SDN NO. 20 KECAMATAN DUNGINGI KOTA GORONTALO - Karim, Herlis Setiawan; Amali, Faysyandri; Umadji, Fadly (Ditlitabmas, Ditjen DIKTI, Kemdikbud RI, 2013)
Language is a cultural component that must be nurtured, maintained and dilestaikan by all people, because language is a communication tool to interact with each other. By implementing research in the District SDN 20 Dungingi Gorontalo City, where 80 % of students have not mastered the local language Gorontalo. In fact, Gorontalo language is the identity of an area that is able to distinguish between one tribe to another tribe. Gorontalo language waning, due to the sophistication of the technology, the progress of science and technology and the lack of awareness of the public, especially the students to use the local language. Making KAMSEUPAI (pocket dictionaries as an innovative learning media) Gorontalo is a language -based solution that is appropriate for elementary school students. Because illustrated pocket dictionary is structured in such a way creative and innovative to attract the readers interest in learning the language of Gorontalo. Moreover, packed with a variety of images and animations that interest children and practical and flexible to carry everywhere. The method does is disseminate to school about the importance of using local languages . Next is the executor of designing dictionaries, edit and distribute them to students at SDN 20, then continued with the Teaching and Learning activities use Kamseupai Gorontalo language and culture. Making this kamseupai as local media innovation language learning for children and as an attempt to reexistence the usage of Gorontalo language which are fading in the community.